Application of innovative remediation processes to mining effluents contaminated by heavy metals - Ubaldini S. (2013)
This work was supported by Italian National Council Researches by Joint Project n.1 of the CNR/SAV Agreement 2010/2012 and under project CNR RSTL n.0042.0005; by Joint Project n. 2 of the CNR/CONCYTEC (Perù), Agreement 2009/2011 Slovak Research and Development Agency under the contract n. SRDA-0252-10; the Scientific Grant Agency No. 2/0166/11 and by the Operational Programme Research and Development through the project: Centre of Excellence for Integrated Research of the Earth's Geosphere (ITMS: 26220120064), which is co-financed through the European Regional Development Fund